Deciphering the d-/l-lactate-producing microbiota and manipulating their accumulation during solid-state fermentation of cereal vinegar. (December 2020) - Chai, Li-Juan; Shen, Mi-Na; Sun, Jia; Deng, Yong-Jian; Lu, Zhen-Ming; Zhang, Xiao-Juan; Shi, Jin-Song; Xu, Zheng-Hong
Abstract: Symphony orchestra of multi-microorganisms characterizes the solid-state acetic acid fermentation process of Chinese cereal vinegars. Lactate is the predominant non-volatile acid and plays indispensable roles in flavor formation. This study investigated the microbial consortia driving the metabolism of D-/l -lactate during fermentation. Sequencing analysis based on D-/l -lactate dehydrogenase genes demonstrated that Lactobacillus (relative abundance: > 95%) dominated the production of both d -lactate and l -lactate, showing species-specific features between the two types. Lactobacillus helveticus (>65%) and L. reuteri (~80%) respectively dominated l - and d -lactate-producing communities. D-/l -lactate production and utilization capabilities of eight predominant Lactobacillus strains were determined by culture-dependent approach. Subsequently, D-/l -lactate producer L. plantarum M10-1 (d :l  ≈ 1:1), l -lactate producer L. casei 21M3-1 (D:L ≈ 0.2:9.8) and D-/l -lactate utilizer Acetobacter pasteurianus G3-2 were selected to modulate the metabolic flux of D-/l -lactate of microbial consortia. The production ratio of D-/l -lactate was correspondingly shifted coupling with microbial consortia changes. Bioaugmentation with L. casei 21M3-1 merely enhanced l -lactate production, displaying ~4-fold elevation at the end of fermentation. Addition of L. plantarum M10-1 twice increased both D- and l -lactate production, while A. pasteurianus G3-2 decreased the content of D-/l -isomer. Our results provided an alternative strategy to specifically manipulate the metabolic flux within microbial consortia of certain ecological niches. Graphical abstract: Image 1 Highlights: D-/l -lactate contents were determined in cereal vinegar production. Putative D-/l -lactate producers were respectively explored during fermentation. Lactobacillus isolates showed species-specific D-/l -lactate production capabilities. Modulation of D-/l -lactate metabolic flux of microbial consortia was performed. An alternative strategy was provided to redistribute the task of community members.